2022
DOI: 10.1039/d2ma00082b
|View full text |Cite
|
Sign up to set email alerts
|

Dual CEA/CD44 targeting to colorectal cancer cells using nanobody-conjugated hyaluronic acid-modified mesoporous silica nanoparticles with pH- and redox-sensitivity

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death among all malignancies. Drug delivery targeting tumor surface receptors improves therapeutic effects and lowers side-effects since it can increase...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Several studies have demonstrated improved delivery when a nanoparticle is actively targeted to CEA in colorectal cancer cells using site specific reagents such as antibodies, antibodyfragments, aptamers, peptides and nanobodies. [35][36][37][38][39] To date, the anti-CEA antibody has shown the most promising targeting bioreceptor in colorectal murine models but translation to clinical application was complicated by the immunogenicity and the clearance from bloodstream, both owing to binding of Fc receptor-containing entities to the antibody Fc region. 40 In addition, antibody size (∼150 kDa) makes cell penetration difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated improved delivery when a nanoparticle is actively targeted to CEA in colorectal cancer cells using site specific reagents such as antibodies, antibodyfragments, aptamers, peptides and nanobodies. [35][36][37][38][39] To date, the anti-CEA antibody has shown the most promising targeting bioreceptor in colorectal murine models but translation to clinical application was complicated by the immunogenicity and the clearance from bloodstream, both owing to binding of Fc receptor-containing entities to the antibody Fc region. 40 In addition, antibody size (∼150 kDa) makes cell penetration difficult.…”
Section: Discussionmentioning
confidence: 99%